2020
DOI: 10.1021/acs.organomet.0c00065
|View full text |Cite
|
Sign up to set email alerts
|

(Isonitrile)platinum(II) Complexes of an Amido Bis(N-heterocyclic carbene) Pincer Ligand

Abstract: Five Pt(II) complexes bearing a 3,6-di-tert-butyl-1,8-bis(1H-imidazol-1-yl)-9H-carbazole (BIMCA) backbone and different isonitrile ancillary ligands were synthesized and photophysically characterized. The solid-state structures were determined by X-ray crystallography, all of which showed a distorted-square-planar geometry where isonitrile moieties protrude from the Pt−carbazole plane. In the solid state, these complexes show biexponential phosphorescence with lifetimes up to 25 ms and quantum yields ranging f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Square planar d 8 platinum complexes have recently drawn considerable interest because of their intriguing light-emitting and assembly properties. Platinum complexes often display phosphorescent emissions due to the strong spin–orbit coupling of the platinum atom. By tuning the ligand structure and coordination mode, full-color emissive platinum complexes have been synthesized and investigated. The assembly properties of platinum complexes are mostly associated with their tendency to form π–π and Pt–Pt interactions upon aggregation. In this context, a great number of platinum complexes have been reported to display appealing assembly behavior with tunable emission properties. …”
Section: Introductionmentioning
confidence: 99%
“…Square planar d 8 platinum complexes have recently drawn considerable interest because of their intriguing light-emitting and assembly properties. Platinum complexes often display phosphorescent emissions due to the strong spin–orbit coupling of the platinum atom. By tuning the ligand structure and coordination mode, full-color emissive platinum complexes have been synthesized and investigated. The assembly properties of platinum complexes are mostly associated with their tendency to form π–π and Pt–Pt interactions upon aggregation. In this context, a great number of platinum complexes have been reported to display appealing assembly behavior with tunable emission properties. …”
Section: Introductionmentioning
confidence: 99%
“…Carbene ligands, mostly the N-heterocyclic carbenes (NHCs), are among the important ligands that have attracted much attention in organometallic chemistry and homogeneous catalysis. Many groups are interested in the preparation of new NHC ligands and their metal complexes to explore their reactivity in catalysis, photophysics, and medicinal chemistry. Among these NHC ligands are bis-NHC ligands, which comprise pairs of NHC rings connected by a methylene linker. …”
Section: Introductionmentioning
confidence: 99%
“…Gray and co-workers constructed another family of N-heterocyclic carbene Pt­(II) complexes 45 – 53 displaying a BIMCA pincer ligand (BIMCA = bis-imidazolylcarbazolate) and isonitrile or acetylides as ancillary ligand (Figure ). The BIMCA ligand contains an organic carbazole chromophore, to which are directly attached two NHC units, generating a rigid (ĈN̂C) pincer ligand around the Pt­(II) center. , Owing to steric factors around the metal center, the X-ray structures of these complexes showed that the metal is tetra-coordinated displaying a distorted tetrahedral geometry instead of a square-planar structure.…”
Section: Luminescent Platinum(ii) Complexes With N-heterocyclic Carbe...mentioning
confidence: 99%